GPR75 mediates hyperuricemia-induced endothelial inflammatory injury via a HOTAIR/miR-141-3p regulatory network - Jiawu Fu; Junbing He; Keshen Li; Manting Zhang; Jiekai Li; Yuchun Liu; Yusen Chen; Wei Bi (Molecular Biology Reports, 2026)

Biomass-derived porous carbon supported Cu₃P/TiO₂ N-doped heterojunction for visible-light photocatalysis - Tingxuan Xie; Manting Zheng; Qingdong Deng; Weixi Zhang; Shenyi Liang; Wei Li; Yinli Dai; Jiaqi Zhang; Xu Feng; Zhanlin Wang; Junhao Li; Runjing Li; et al. (Colloids and Surfaces C: Environmental Aspects, 2026)

Developmental and behavioral toxicity of citalopram in zebrafish early life stages: Neurochemical alterations, oxidative stress responses, and transcriptomic signatures - Yanhua Liu; Manting Li; Jianqiu Yu; Fanrui Yu; Leilei Lu; Jianqiu Chen; Ruixin Guo (Aquatic Toxicology, 2026)

Trace elements in surface sediments along the Shenzhen coast, South China: Spatial-seasonal patterns, ecological risk, and PMF-based source apportionment - Cheng Chen; Ziliang Chen; Pujiang Huang; Liangming Wang; Binbin Shan; Yan Liu; Yingbang Huang; Zaiwang Zhang; Qijian Xie; Manting Liu; Dianrong Sun; Changping Yang (Regional Studies in Marine Science, 2026)

Ambient ozone exposure associated with incidence and accelerated occurrence of cardiometabolic diseases and potential mediating effect of blood pressure: A prospective cohort study based on the GOLD-Health - Zhonghua Ai; Hui Liu; Weiquan Lin; Peng Hu; Qin Zhou; Fei Tian; Manting Rao; Zitong Zhuang; Xiangyi Liu; Shengtao Wei; Aaron M. Qian; Hualiang Lin; et al. (Atmospheric Environment, 2026)

Neurodevelopmental toxicity of black carbon in zebrafish: behavioral and metabolomic insights - Fanrui Yu; Yanhua Liu; Manting Li; Yaqian Gao; Leilei Lu; Jianqiu Chen; Ruixin Guo (Aquatic Toxicology, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

Multi-indices decision-making incorporating environmental capacity for assessing brownfield sites safety - Jianfang Wu; Xinfu Chen; Chen Chen; Manting Liu; Shen Wang; Ci Zhao (Environmental Geochemistry and Health, 2025)

Self-assembly of tea polyphenol onto the high strength chitosan film fabricated via a new way to enhance the antioxidant and antibacterial activity for meat preservation - Yuntao Wang; Xiuqin Guo; Zhilong Qin; Rongqin Liu; Shengjie Li; Manting Du; Si Qiu; Yanhong Bai (Food Packaging and Shelf Life, 2025)

Soil organic matter components and sesquioxides integrally regulate aggregate stability and size distribution under erosion and deposition conditions in southern China - Geng Guo; Yu Kong; Yanyin Xu; Xiaoying Peng; Manting Niu; Guangruo Zeng; Zhen Ouyang; Jun Liu; Chen Zhang; Jie Lin (Journal of Hydrology, 2024)

Optimization of water quality evaluation index using information sensitivity method and variable fuzzy model for the Guo River, China - Shuoya Cheng; Peigui Liu; Mei Yao; Mei Li; Meng Liu; Manting Shang (Environmental Science and Pollution Research, 2024)

Microsatellite-Marker-Based Evaluation of Stock Enhancement for Kuruma Prawn Penaeus japonicus in Beibu Gulf, South China Sea - Mengyi Zhang; Yu Zhao; Binbin Shan; Yan Liu; Changping Yang; Liangming Wang; Manting Liu; Qijian Xie; Yuan Li; Jianwei Zou; Dianrong Sun (Fishes, 2023)
The objectives of this study were to evaluate the effect of stock enhancement on Penaeus japonicus (Bate, 1888) in Beibu Gulf, South China Sea, and to investigate whether stock enhancement has genetically affected the natural population of P. japonicus in the Beibu Gulf waters. Five microsatellite loci were used to identify released individuals among recaptured specimens. In total, 13 of the 487 recaptured individuals were found with their corresponding parents for this release of shrimp seedlings, accounting for 2.67% of the total recaptured P. japonicus. Furthermore, it was determined that the genetic differences among the broodstock, released, and recaptured populations of P. japonicus were small and did not cause significant changes in the genetic structure of P. japonicus in the area. In conclusion, the stock enhancement of P. japonicus in Beibu Gulf had a certain effect on resource restoration, and there is no difference in the genetic characteristics obtained by the microsatellite markers compared to the original population in this area.

Ecological Niche and Interspecific Association of the Main Fishes in the Coastal Waters of Hainan Island, China - Zhengli Luo; Yanbo Zhou; Ning Liu; Liangming Wang; Yan Liu; Binbin Shan; Manting Liu; Cheng Chen; Changping Yang; Dianrong Sun (Fishes, 2023)
This study explored the ecological niche and interspecific relationships among the main fish species in the coastal waters of Hainan Island based on data from fishery stock surveys conducted in the spring and autumn of 2022. The methods of chi-square test, percentage of co-occurrence (PC), association coefficient (AC), cluster analysis, and redundancy analysis were used to analyze the interspecific associations and influence of environmental factors on the ecological niches of fish communities. According to the cluster analysis of niche breadth, 20 main fishes could be divided into broad, medium, and narrow niche species. There were four and eight broad niche species in spring and autumn, respectively. The ranges of niche overlap values were 0.001–0.91 in spring and 0–0.87 in autumn, indicating that the species differed and were similar in their ability to utilize resources, survive in habitats, and prey. According to the variance ratio and statistic value W, the main fishes in spring showed a significant positive association, whereas those in autumn showed a positive association, but not at a significant level, indicating that the main fishes in spring were more closely associated with each other. There were 56 species pairs in the 2 seasons that were significantly associated (χ2 ≥ 3.841). AC and PC tests revealed that the interspecific association was strong and tended to be positive. According to the redundancy analysis, environmental factors such as surface temperature, water depth, and pH significantly affected the main fishes in spring, while environmental factors such as dissolved oxygen, bottom temperature, surface salinity, and pH significantly affected those in autumn.

Paris saponin Ⅰ induce toxicity in zebrafish by up-regulation of p53 pathway and down-regulation of wnt pathway - Boran Ni; Wenping Wang; Manting Liu; Yuchen Xu; Jinxi Zhao (Toxicon, 2023)

Organophosphate ester exposure among Chinese waste incinerator workers: Urinary levels, risk assessment and associations with oxidative stress - Xiaoling Wu; Duo Zhang; Yining Chen; Junchun Shen; Xiangyu Li; Quanzhi Zheng; Jiaojiao Ma; Jiayi Xu; Manting Rao; Xiang Liu; Shaoyou Lu (Science of The Total Environment, 2023)

Groundwater Nitrate Bioremediation Simulation of In Situ Horizontal Well by Microbial Denitrification Using PHREEQC - Peigui Liu; Gang Wang; Manting Shang; Mingchao Liu (Water, Air, & Soil Pollution, 2021)

Effect of the membership function type on the fuzzy risk of allowable groundwater drawdown calculation results - Peigui Liu; Su Zhang; Manting Shang (Stochastic Environmental Research and Risk Assessment, 2021)

Responding to environmental pollution-related online posts: behavior of Web surfers and its influencing factors - Yong Liu; Manting Li; Juanjuan Zhao; Haidong Yu (Environment, Development and Sustainability, 2019)

Horizontal Well Test for Simulating the In Situ Remediation of Nitrate Contaminated Groundwater by Microbial Denitrification - Peigui Liu; Mingchao Liu; Manting Shang; Xingyuan Yi (Water, Air, & Soil Pollution, 2019)